P-195 Palliative care as an intrinsic part of integrated care – does the model fit?. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Brannan, Carolanne; Dodds, Nigel
Abstract : Introduction: Integrated Care(IC) (Ham and Alderwick, 2015) is a model of delivering health and social care, adopted by a number of Clinical Commissioning Groups across East London. This facilitates professionals to work with their external partners, to streamline the patient pathway, and improve patient outcomes. Within this model it is expected that multi-professional teams within the acute and community services, spanning all disciplines, work in collaboration by meeting regularly to proactively plan holistic, person-centred care, rather than focus on separate diseases or co-morbidities, or psycho-social issues, thus aiming to avoid working in silos, in relation to patient care. Aims: One of the main aims of IC is to work towards agreed strategies to avoid hospital admission, and support patients to remain in their own homes. St Joseph's Hospice community palliative care team are active partners in the integrated care teams, and work with other health and social care providers to ensure patients in the last years of life are enabled to be cared for, and die in their preferred place. Methods: In this presentation we will describe how all relevant professional groups, from all care settings, and involved in patient care meet monthly within every GP practice across the borough in Integrated Care meetings. The focus of these meetings is patient focused, where the most vulnerable patients within the practice are discussed, and a holistic plan of care is agreed using the knowledge and expertise of all the professionals present. This model has replaced palliative care specific meetings where the meeting was focused only on patients approaching the end of life. Through these changes, we will demonstrate the changing nature of referrals to the community palliative care team, which may have implications for the future direction of the hospice.